2020
DOI: 10.3389/fbioe.2019.00450
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Wearable Upper Limb Assistive Devices in Degenerative Neuromuscular Diseases: A Systematic Review and Meta-Analysis

Abstract: Background: This systematic review summarizes the current evidence about the effectiveness of wearable assistive technologies for upper limbs support during activities of daily living for individuals with neuromuscular diseases. Methods: Fourteen studies have been included in the meta-analysis, involving 184 participants. All included studies compared patients ability to perform functional tasks with and without assistive devices. Results: An overall effect size of 1.06 (95% CI = 0.76-1.36, p < 0.00001) was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Our analysis shows that muscle activity and joint mobility are affected by load reduction, but their relation has not been investigated nor linked to ADL performance. Gandolla et al, deducted similar conclusions from their focus on activity and participation [34]. Therefore, we recommend to investigate the relation between the two ICF components in a biomechanical framework under various levels of load reduction during functional tasks to optimise effort reduction and mobility improvements during common ADLs.…”
Section: Research Recommendationsmentioning
confidence: 66%
See 2 more Smart Citations
“…Our analysis shows that muscle activity and joint mobility are affected by load reduction, but their relation has not been investigated nor linked to ADL performance. Gandolla et al, deducted similar conclusions from their focus on activity and participation [34]. Therefore, we recommend to investigate the relation between the two ICF components in a biomechanical framework under various levels of load reduction during functional tasks to optimise effort reduction and mobility improvements during common ADLs.…”
Section: Research Recommendationsmentioning
confidence: 66%
“…The perceived benefits, which vary between users, can even decrease so much over time that the user decides to stop using the device completely. Similarly, a recent systematic review on the short-term benefits of wearable devices found that as the disability level changes the device benefits change as well [34].…”
Section: Adaptations Over Timementioning
confidence: 97%
See 1 more Smart Citation
“…However, they are also prone to bias, e.g., self-reported duration of DAS use was found to depend heavily on users’ expectations of, and reliance on, the device [ 6 , 9 ]. Similar bias was also present in studies evaluating the functional improvement where a patient’s perceived gain was higher than the gain detectable through clinical scales [ 22 ]. The low level of specificity and the bias in self-reports makes it difficult to distil the most important aspects of DAS usage [ 21 ].…”
Section: Introductionmentioning
confidence: 66%
“…In the last years, the PUL module has been widely applied in DMD clinical trials [ 12 , 17 20 ], but it has been rarely used in other dystrophies [ 21 ]. A previous study evaluated PUL 1.2 module in a group of 322 DMD boys and adults [ 10 ], showing that this scale is an excellent tool to assess both ambulant and non-ambulant DMD patients’ upper limb functionality.…”
Section: Introductionmentioning
confidence: 99%